Analisis Asas Hukum Pidana Islam Dan Asas Hukum Pidana Di Indonesia - Jafar, Wahyu Abdul (Al-Istinbath: Jurnal Hukum Islam, 2016)
This articlehas done to identifysome similarities and differences between the principles of Islamic criminal law and ones of criminal law in Indonesia. The Differences and similarities among both occurred because each law has different legal sources. Actually, The data presented in this article comes from information sources that relates directly to the Islamic criminal law and positive-criminal law in Indonesia. From this study,we know that there are some principles that are different meanwhile there are also some principlesin both, the Islamic criminal law and the criminal law in Indonesia,nevertheless it does not mean exactlysame because of their applicabilities. As well as the differences of both do not mean absolutely different because of their substances. The same principles amongones of Islamiccriminal law and criminal law in Indonesia, they are the principle of legality, the presumption of innocence and the principle of not retroactivepenalties. Meanwhile, the different principlesamong both are the principle of the prohibition of analogy, the principle of territoriality, the principle of nationality, the principleof personality, the principle of universality, the principle of changes in legislation, the principle of equality in the law and the principle of the prohibition of transferingfaults on others.